2019
DOI: 10.25105/cesd.v1i2.4197
|View full text |Cite
|
Sign up to set email alerts
|

Manfaat Penggunaan Building Information Modelling (Bim) Pada Proyek Konstruksi Sebagai Media Komunikasi Stakeholders

Abstract: <span><em>Construction projects are becoming much more complex and difficult to manage, reciprocal </em><span><em>interdependence between stakeholders is one of the causes, such as architects, civil engineers and </em><span><em>mechanical. Building Information Modelling (BIM) not only allows the geometrical modelling butalso useful </em><span><em>for management of construction project especially in communication between stakeholders. The aims of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
3
0
7
Order By: Relevance
“…The criteria for reliability tests are Cronbach alpha values over 0.6 which means they have a strong relationship. Ref [4] Ref [5] Ref [12] Ref [6] Ref [7] Ref [13] Basic Understanding about BIM Knowledge of the concept of BIM in the world of construction…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for reliability tests are Cronbach alpha values over 0.6 which means they have a strong relationship. Ref [4] Ref [5] Ref [12] Ref [6] Ref [7] Ref [13] Basic Understanding about BIM Knowledge of the concept of BIM in the world of construction…”
Section: Methodsmentioning
confidence: 99%
“…The benefits of using BIM in construction projects as a means of communication among stakeholders [4]. The results showed that BIM can be effectively used as a means of communication among stakeholders to improve collaboration and information sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Tantangan lain menurut Alaloul et el (2018) yaitu mengadopsi metode digital seperti Building Information Modelling (BIM), dalam proses produksi pada bidang konstruksi (Alaloul et al, 2018). Selain hal di atas, metode BIM juga dimanfaatkan sebagai media komunikasi efektif oleh stakeholder dalam kegiatan konstruksi (Raflis et al, 2019). Ini menandakan bahwa kegiatan konstruksi selain menuntut ketepatan waktu, biaya dan mutu tentu menuntut adanya koordinasi dan komunikasi yang efektif antar disiplin ilmu dalam sebuah kegiatan.…”
Section: Pendahuluanunclassified
“…Beberapa faktor yang menyebabkan kurangnya keakuratan perhitungan QTO berbasis CAD konvensional yaitu kesalahan dalam pemindahan data antar file, resiko perhitungan ganda dan elemen yang hilang, gambar 2D mengandung banyak kesalahan yang menyebabkan masalah lebih lanjut [4]. Dengan mengimplementasikan BIM merupakan salah satu cara untuk mendukung pertumbuhan infrastruktur dinegara ini karena dapat meminimalisir kesalahan dalam proyek konstruksi [5] [6]. Pada proyek Jalan Tol "X" ini merupakan jenis pekerjaan konstruksi jalan dan jembatan yang wajib untuk menerapkan BIM hal ini sesuai dengan Surat Edaran No.…”
Section: Pendahuluanunclassified